Enhancing the Role of Women in Water User Associations in Azerbaijan - Merkle, R.; Meerbach, D.; Akhmedova, A.; Bagirzadeh, M.; Dideron, S.; Javazadeh, L.; Rustamova, S. (World Bank, Washington, DC, 2013)
The purpose of this report on enhancing the role of women in water user associations in Azerbaijan is to provide guidance for mainstreaming gender in irrigation management projects in Azerbaijan and in the wider Caucasus and Central Asian regions in order to foster efficient and equitable development in irrigation management. The paper is divided in three chapters. Chapter one sets the background relating the themes of gender to water users associations (WUAs) and irrigation agriculture. It provides both the general sector background as well as an introduction of the overall study and research that was undertaken at the end of Irrigation Distribution System and Management Improvement Project (IDSMIP). Chapter two provides the informative basis for enhancing the role of women in irrigation management. It analyses and discusses the role of men and women in irrigation agriculture in Azerbaijan by synthesizing the findings of the gender survey. Chapter three provides lessons for WUAs in Azerbaijan on how to promote gender equity and for World Bank projects on how to operationalize gender mainstreaming in irrigation agriculture in the country. It also provides guidance in establishing an enabling environment that will foster gender equity in similar irrigation sector programs in the wider Caucasus and Central Asian region.